Plural School - Miranda, Glaura Vasques de (Estudos Avançados, 2007)
This paper presents the Plural School, implemented in Belo Horizontes local educational system from 1993 to 1996. This educational proposal has been considered innovative by many people and polemical by others since it attempted to break the traditional culture of public schooling, inserting a broader, democratic, inclusive and plural concept of education. It also attempted to take the multiple dimensions of an individuals edification into account and to supply adequate conditions for children from lower socia classes to succeed. Moreover, it aimed at meeting the demands of public policies in order to expand elementary and middle level education and, above all, improve the quality of public schools. The article presents the proposal, some polemics involving it and its assessment results.